Comparison of Inverse Kinematics and Forward Kinematics Methods on Walk Cycle Animation Characters - Afifah Nur Aini; Ema Utami; Suwanto Raharjo (Telematika, 2021)
The 3D animation industry is currently growing rapidly, but the process of animating 3D characters is not always fast, because it is often constrained at the animation stage due to the complexity or irregularity of the function of each rig on the 3D character object, therefore it takes a proper rig creation stage to support the animation process that is more efficient in terms of process and time. Kinematics in animation is used for reference when an object is moving. The animation uses a Kinematics approach to display natural results. This research aims to study the level of effectiveness in terms of the time span required to drive the 3D Walk cycle animation using the attached Kinematics & Advanced Kinematics methods. The animation reference used was a standard human Walk cycle with the extent for each part of the body to be animated such as head animation, hand animation, foot animation, and bed animation to complete a walking compilation of animated Walk cycle. The execution of each part is carried out by the inverse kinematics method and then proceed with the advanced kinematics method. Based on the results of the implementation in each section of the walk cycle by comparing the two methods, Inverse Kinematics is an effective method for animating the legs and the head. While the Forward Kinematics method is more effective in animating the hands, body parts, and finishing movement. The results of the comparison show that the level of time effectiveness in human character 3D animation movements using the inverse kinematics method compared to forward kinematics are 31.18% in body animation, 40.46% in foot animation, 13.94% in hand animation, 2.04% in head animation motion, and 7.61% for finishing walk cycle movement.